2016
DOI: 10.11604/pamj.2016.24.96.9282
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia in pregnant adolescent girls with malaria and practicing pica

Abstract: IntroductionPregnancy during the adolescent period is challenging mainly because of the nutritional demands of both the adolescent and pregnancy period. The risk for anaemia increases especially in developing countries such as Ghana where malaria is endemic and the practice of pica is common. In this study, we sought to determine the prevalence of anaemia, pica practice and malaria infection among pregnant adolescent girls and assess the extent to which these factors are associated.MethodsTwo hundred and sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
11
2
Order By: Relevance
“…This study aimed to highlight the degree of malaria-induced and non-malaria-induced anemia in different age groups, different trimesters and in varying gravidity among pregnant women living in communities along the Lagoon coast in Lagos Nigeria. It should be appreciated with great concern that majority of the approximate 500,000 women who die annually in pregnancy occur most in the developing world 27,28 that are mostly malaria-endemic. Malaria and anemia in any stage of pregnancy are almost always devastating to the fetus, the mother, the family and the community.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to highlight the degree of malaria-induced and non-malaria-induced anemia in different age groups, different trimesters and in varying gravidity among pregnant women living in communities along the Lagoon coast in Lagos Nigeria. It should be appreciated with great concern that majority of the approximate 500,000 women who die annually in pregnancy occur most in the developing world 27,28 that are mostly malaria-endemic. Malaria and anemia in any stage of pregnancy are almost always devastating to the fetus, the mother, the family and the community.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence also varies from country to country and from region to region within same countries. Studies have shown that the prevalence of AIP is as high as 99% among women in tertiary facility in India, [20] 90.5% in urban Pakistan,9 76% among pregnant adolescents in Ghana [21], 39.9% in south Ethiopia, [8] 47.4% in northern Tanzania [4] to as low as 2.2% among pregnant women with early pregnancy in New Zealand. [22] In Nigeria, the overall prevalence of anaemia among pregnant women is put at 57.8% [1] while studies have documented regional prevalence of 54.5% in Uyo South South Nigeria, [3] 56% in Abakiliki in south east Nigeria, [5] 39.2% in Sokoto north western Nigeria, [7] 76.5% in Abeokuta, south western Nigeria, [12] 71.3% in Azara in north east Nigeria, [23] and 60.4% in a tertiary facility in Ilorin, north central Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Yet there was a marginal increase in coverage in the Volta Region from 30% to 31% and no change in per cent coverage in the Northern Region (at 14%) in the 6-year period (GSS, GHS, & ICF International, 2015;GSS, GHS, & ICF Macro, 2009). Many of the studies on anaemia in Ghana have been limited to assessing prevalence and determining risk factors among pregnant women (Engmann et al, 2008;Glover-Amengor et al, 2005;Intiful et al, 2016;Mockenhaupt et al, 2000;Stephens et al, 2014). There is a paucity of evidence on perceptions of anaemia in Ghanaian communities and hence a limited understanding of gaps in local knowledge and how this could potentially drive the burden of anaemia as well as efforts to reduce its prevalence.…”
mentioning
confidence: 99%